Analisis Penentuan Harga Jual Produk Dengan Menggunakan Metode Cost Plus Pricing pada UMKM Tahu Maju Lancar - Hofifah Subhan, Ika; suyanto, suyanto; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2024)
This study aims to identify and analyze production costs in order to determine the seling price of the”Tofu Maju Lancar” product. The method utilized is the cost pluspricing approach with the full costing method, ensuring that the selling price is set effectively to generate optimal profits. This research employs a qualitative approach and utilizes descriptive research techniques. The focal point of this research is the company “Tofu Maju Lancar”, which operates as a tofu producer. The primary objective of this study is to gather pertinen data concerning production costs. The focus of this research encompasses the costs associated with the entire production process. The findings of this study indicate that while the cost plus pricing method using UMKM calculations does yield profits, the home industry is unable to attain the anticipated 50% profits due to generated profits remaining insufficient to cover the factory overhead costs that must be shouldered.